Analysis Of Accounting Treatment Of Rahn (Pay Gold) Financing Practices Based On PSAK 107 (Ijarah) - Moh. Sari Sam (JEKAMI Journal of Accounting, 2021)
The aims of this study to determine the suitability of the accounting practice of rahn financing (gold pawning) with PSAK 107 (Ijarah) and the rules of gold pawning practice based on DSN Fatwa No.26/DSN-MUI/IIl/2002 on the Batangkaluku sharia pawnshop. This type of this research is a qualitative descriptive study by taking a case study at PT. Batangkaluku Sharia Pawnshop. Sources of data used are primary data and secondary data, with data collection by library research and field research, namely observation, interviews, documentation, and Internet searching. The main instruments in this study used interview lists, notebooks, voice recorders, cameras and stationery. The analytical techniques applied are data collection, data reduction, data presentation, and drawing conclusions. The results of this study that the accounting practice at is not yet fully compliant with PSAK 107 which includes recognition and measurement, presentation and disclosure because the pawnshop does not charge for repairs to the object of ijarah. PT. Pegadaian Syariah Batangkaluku is sharia pawnshop only inputs transaction data and automatically goes online to the regional VI Makassar head office server. However, in practice the sharia gold pawn is in accordance with the Sharia Council Fatwa No.25/DSN-MUI/III/2002 concerning rahn, namely gold rahn may be used based on the ar-rahn principle, the costs of storing goods ( marhun) are borne by the pawner (rahin), and the cost of storing goods (marhun) is carried out based on the ijarah agreement.